Perkembangan Ekonomi dan Keusahawanan Menerusi Dana Zakat di Kedah - Nur Idientee, Abd Halim (2011)
Zakat one of 'Rukun Islam'. Zakat have a fuction to close the relationships between people base on social class. In this research, researcher want to know, Zakat can help awnaf to make better life and in the same time give the positive effect to economic and entrepreneurships. To finished this research, researcher use two type of data collection. Type of data collection is qualitative and quantitative and to get the finding in this research, researcher need to combine between two type of data collection. The finding in this research is researcher want to conclude zakat is one of media to help awnaf to make a better life and grow economic and entreprenuerships.